Simulation of settling of solid particles due to sudden impeller stoppage - Sardeshpande, Madhavi V.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2012)
Stirred tank reactors (STRs), which are used in process industries (for a variety of operations, such as catalytic reactions, dissolution of a solid, crystallization, and so on), often involve handling of solid liquid (gas) systems. The solid suspension and the quality of the suspension are key issues in the design and operation of such stirred reactors. Despite extensive experimental work over previous decades, comprehensive understanding and reliable methods to predict the solids suspension and the quality of the suspension are not yet available. Advances in computational fluid dynamics (CFD) and new experimental techniques offer potentially effective ways of understanding solids suspension in stirred tanks. The present work highlights the potential of using transient measurements by way of the dynamic settling of solid particles because of the sudden stoppage of an impeller to evaluate CFD models. Sudden impeller stoppage results in significantly different conditions, in terms of the ratio of particle diameter to Kolomogorov length scale (d(p)/lambda), as well as the solids volume fraction experienced by solid particles. Therefore, experimental data under such sudden impeller stoppage offer a better way to evaluate the influence of prevailing turbulence and solids volume fraction on effective drag and therefore offer a more-stringent test to CFD models than steady-state profiles. Besides facilitating the development of computational models, the experimental and simulation studies of sudden impeller stoppage also provide useful data to gain insight into the behavior of the stirred tank after abrupt impeller stoppage due to sudden power failure.